(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2023)
The paper aims to be a first survey on the editorial practices implemented by the judicial curiae of the three suburban Podestariae of the medieval Genoese system. The analysis intends to detect points of contact and divergences of the surviving fourteenth-century registers, in order to highlight any shared management policies regarding documentary models and to identify the emerging traits of the professional profiles involved.